2015
DOI: 10.3109/13880209.2015.1038755
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing potential of naringin ointment formulation via regulating the expression of inflammatory, apoptotic and growth mediators in experimental rats

Abstract: Context: Wound healing is a consequence of a complex process involving inflammatory, proliferative, and remodeling phases. Naringin, a flavanone glycoside, is associated with modulation of various oxido-inflammatory and growth factors. Aim: The aim of this study is to evaluate the wound-healing activity of naringin ointment formulation (NOF) on experimental wound models. Materials and methods: A soft paraffin-based cream containing 1, 2, and 4% (w/w) naringin was formulated and evaluated for physicochemical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(52 citation statements)
references
References 76 publications
(81 reference statements)
0
51
0
1
Order By: Relevance
“…In rats with spinal cord injury treatment with naringin at 20 or 40 mg/kg increased levels of VEGF expression suggesting that naringin is a neurotrophic factor under these conditions (Rong et al, 2012). A wound healing ointment containing 2% and 4% naringin has also been shown to stimulate collagen I synthesis and VEGF levels thereby promoting angiogenesis (Kandhare et al, 2016). Song et al (2017) have also shown naringin’s ability to promote angiogenesis and bone healing through stimulation of VEGF/VEGFR-2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In rats with spinal cord injury treatment with naringin at 20 or 40 mg/kg increased levels of VEGF expression suggesting that naringin is a neurotrophic factor under these conditions (Rong et al, 2012). A wound healing ointment containing 2% and 4% naringin has also been shown to stimulate collagen I synthesis and VEGF levels thereby promoting angiogenesis (Kandhare et al, 2016). Song et al (2017) have also shown naringin’s ability to promote angiogenesis and bone healing through stimulation of VEGF/VEGFR-2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…58 GSH is a potent ubiquitous, non-enzymatic biological antioxidant 48,59,60 plays a vital role in the detoxification of free radical species such as hydrogen peroxide, superoxide, and alkoxy radicals to maintain the cell metabolism and integrity. 40 The level of glutamine is successfully reduced in renal tissue of rat under stressful conditions. 61 However, glutamine plays an important role in glutathione metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The homogenates were centrifuged at 10,000 g at 0 °C for 20 min. It was divided into aliquot to determine superoxide dismutase (SOD), glutathione (GSH), malondialdehyde (MDA), total calcium content, nitric oxide content, membrane-bound inorganic phosphate enzyme, tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1β and nuclear factor-kappaB (NF-κB) according to previously reported procedures (Adil et al, 2016[1][2]; Kandhare et al, 2016[39], 2012[48]; Visnagri et al, 2015[79]).…”
Section: Methodsmentioning
confidence: 99%